Monetary Policy and Bank Risk-Taking in Sub-Sahara Africa - Aboyadana, Gabriel (The European Journal of Applied Economics, 2021)
Monetary policy has been shown to influence risk taking behaviour of banks in EU and North America. Africa has however received limited attention in this regard. Our study expands the monetary policy-bank risk-taking literature to sub-Sahara Africa by examining a panel of commercial banks from 2001-2015 for different types of risks. We find that monetary policy significantly influences bank risk-taking both statistically and economically but the effect differs across the types of risks. Bank size and profitability are important in determining how effective monetary policy impacts risk-taking. Monetary policy authorities in the sub region should be slow to pursue expansionary monetary policy. Key Words: Risk-taking, Financial Crisis, Monetary Policy, Africa